Strategic Correlation between Good Corporate Governance, Intellectual Capital, and Corporate Social Responsibility with Financial Performance - Ni Putu Pratiwi Ika Dharma Lestari; Eka Ardhani Sisdyani (E-Jurnal Akuntansi, 2025)
Financial performance reflects a company’s overall financial condition. The growth of modern enterprises has intensified business competition, thereby necessitating the establishment of robust governance systems. Intellectual capital, as an intangible asset, plays a critical role in enhancing a company’s ability to generate competitive advantage. In parallel, companies are obligated to implement Corporate Social Responsibility (CSR) initiatives as part of their commitment to sustainable development. The novelty of this research lies in its approach to variable measurement. This study aims to examine the correlation between Good Corporate Governance (GCG), Intellectual Capital (IC), and CSR with financial performance in the banking sector. The sample was selected using a non-probability sampling approach with a purposive sampling technique. Secondary data were sourced from the official website of the Indonesia Stock Exchange and the financial reports of listed banking companies. Data analysis was conducted using STATA. The findings indicate that GCG and CSR do not exhibit a significant correlation with financial performance in the banking sector. Conversely, intellectual capital demonstrates a positive and significant correlation with bank financial performance.